Performance Evaluation of Hypervisors: A Comprehensive Benchmarking Study on VMware, Xen, and KVM - Satalino, Michael; Wu, Hao; Pang, Yulei (2026 3rd International Conference on Computer and Multimedia Technology (ICCMT), 2026)
This research presents a comparative performance analysis of three prominent hypervisor architectures—KVM, Xen, and VMware Workstation—to evaluate their scalability and resource efficiency under increasing virtual machine (VM) densities. Utilizing a standardized benchmarking framework, this study quantifies performance regressing across CPU throughput (GFLOPS), memory bandwidth, disk I/O, and initialization latency. The experiment results reveal that architectural design significantly dictates scalability limits: KVM’s kernel-integrated Type-1 model achieved the highest efficiency, maintaining a near-native CPU baseline and superior I/O resilience at peak density. In contrast, Xen’s microkernel architecture demonstrated stable but lower throughput due to Domain 0 (Dom0) management overhead, while VMware’s Type-2 hosted model exhibited the most acute performance degradation. These results demonstrate that while hosted hypervisors are suitable for low-density personal use, kernel-level integration is a mechanical necessity for maintaining performance in high-concurrency server environments. This work provides a reproducible methodology and critical data for system architects and researchers seeking to optimize resource orchestration in distributed and parallel systems.
Keywords: Central Processing Unit; Cloud Computing; Hardware; Hypervisor Benchmarking; Information rates; KVM; Management information base; Measurement; Memory; Performance Evaluation; Throughput; VMware; Virtual machine monitors; Virtual machines; Virtualization; Xen; dept.csc; dept.mat

Hypergeometric decomposition of Delsarte K3 pencils - Davis, Rachel; Dukes, Jessamyn; Ribeiro, Thais; Orvis, Eli; Salerno, Adriana; Sturman, Leah; Whitcher, Ursula (Research in the Mathematical Sciences, 2026)
Abstract We study five pencils of projective quartic Delsarte K3 surfaces. Over finite fields, we give explicit formulas for the point counts of each family, written in terms of hypergeometric sums. Over the complex numbers, we match the periods of the corresponding family with hypergeometric differential operators and series. We also obtain a decomposition of the incomplete L -function of each pencil in terms of hypergeometric L -series and Dedekind zeta functions. This gives an explicit description of the hypergeometric motives geometrically realized by each pencil.
Keywords: Basic hypergeometric series; Generalized hypergeometric function; Hypergeometric distribution; Hypergeometric function; Pencil (optics); Point (geometry); Quartic function; dept.mat

Change the journal title to reflect evolving focus - Choi, Kyong; Lee, Yujin; Lee, Younhee; hwang, jihyun (Mathematics Education Research and Practice, 2025)
Research in Mathematics Education.This change reflects the journal's expanding scope, integrating both theoretical and practical aspects of mathematics education in alignment with growing interdisciplinary and applied academic trends.In this editorial, we discuss revised scope of MERP and invite contributions from a diverse range of researchers and practitioners
Keywords: Field (mathematics); Focus (optics); Range (aeronautics); Scope (computer science); dept.mat

Incorporating changeable attitudes toward vaccination into compartment models for infectious diseases - Jiang, Yi; Kurianski, Kristin; Lee, Jane; Ma, Yanping; Cicala, Daniel; Ledder, Glenn (Mathematical Biosciences & Engineering, 2025)
We develop a mechanistic model that classifies individuals both in terms of epidemiological status (SIR) and vaccination attitude (Willing or Unwilling/Unable), with the goal of discovering how disease spread is influenced by changing opinions about vaccination. Analysis of the model identifies the existence and stability criteria for both disease-free and endemic disease equilibria. The analytical results, supported by numerical simulations, show that attitude changes induced by disease prevalence can destabilize endemic disease equilibria, resulting in limit cycles.
Keywords: Computer science; Disease; Econometrics; Endemic disease; Environmental health; Epidemic model; Epidemiology; Immunology; Infectious disease (medical specialty); Limit (mathematics); Machine learning; Mathematics; Medicine; Pathology; Stability (learning theory); Vaccination; dept.mat

MaPP Challenge : Giving a Taste of Contemporary Mathematics Research to Secondary Students in a Puzzle‑Based Outreach Program - Lee, Younhee; Carrigan, Braxton; Clontz, Steven; Couch, P.; Jones, Cadavious; Noble, Abby; Owens, Andrew; Pang, Yulei (Mathematics Outreach: Examples and Impact from Across the Globe, 2026)
Keywords: Community‑driven; Event (particle physics); Focus (optics); Focus group; Outreach; Perception; Taste; contemporary mathematics; dept.mat; fostering positive mathematical identity; inclusive mathematical outreach program; puzzle‑ based outreach

Rings with q-torsionfree canonical modules - Endo, Naoki; Ghezzi, Laura; Goto, Shiro; Hong, Jooyoun; Iai, Shin-Ichiro; Kobayashi, Toshinori; Matsuoka, Naoyuki; Takahashi, Ryo (Commutative Algebra, 2025)
Let A be a Noetherian local ring with canonical module KA. We characterize A when KA is a torsionless, reflexive, or q-torsionfree module for an integer q ≥ 3. If A is a Cohen–Macaulay ring, H.-B. Foxby proved in 1974 that the A-module KA is q-torsionfree if and only if the ring A is q-Gorenstein. With mild assumptions, we provide a generalization of Foxby’s result to arbitrary Noetherian local rings admitting the canonical module. In particular, since the reflexivity of the canonical module is closely related to the ring being Gorenstein in low codimension, we also explore quasinormal rings, introduced by W. V. Vasconcelos. We provide several examples as well. ©2025 Walter de Gruyter GmbH,Berlin/Boston.
Journal Abbreviation: De Gruyter Proc. Math.
Keywords: Algebra over a field; Canonical module; Class (philosophy); Cohen–Macaulay ring; Gorenstein ring; Representation (politics); Set (abstract data type); dept.mat; q-Gorenstein ring; q-torsionfree module; quasinormal ring

Hilbert coefficients and Sally modules: a survey of Vasconcelos’ contributions - Hong, Jooyoun; Morey, Susan (Commutative Algebra, 2025)
Keywords: Chern numbers; Data collection; Field (mathematics); Hilbert coefficients; Hilbert functions; Hilbert polynomials; Sally modules; Work (physics); dept.mat; multiplicity

Degrees: Vasconcelos contributions - Ghezzi, Laura; Hong, Jooyoun (De Gruyter Proc. Math., 2025)
A degree of a module M is a numerical measure of information carried by M. We highlight some of Vasconcelos’ outstanding contributions to the theory of degrees, bridging commutative algebra and computational algebra. We present several degrees he introduced and developed, including arithmetic degree, jdeg, homological degree, cohomological degrees, canonical degree, and bicanonical degree. For the canonical and bicanonical degrees, we discuss recent developments motivated by our joint works [25, 19, 9]. ©2025 Walter de Gruyter GmbH,Berlin/Boston.
Journal Abbreviation: De Gruyter Proc. Math.
Keywords: Multiplicity; arithmetic degree; bicanonical degree; canonical degree; canonical ideal; cohomological degree; dept.mat; homological degree; jdeg

Toward Resolving Kang and Park’s Generalization of the Alder–Andrews Theorem - Sturman, Leah; Swisher, Holly (La Matematica, 2026)
Keywords: Alder–Andrews theorem; Alder’s conjecture; Conjecture; Generalization; Inequality; Kang-Park conjecture; Partition (number theory); Rogers–Ramanujan identities; Type (biology); d-distinct partitions; dept.mat

Skolem Number of Kagome Lattice Graphs - Carrigan, Braxton; Martone, Max (Theory and Applications of Graphs, 2025)
A proper Skolem labelling of a graph G is a function assigning a positive integer to each vertex of G such that any two vertices assigned the same integer are that distance apart in the graph. The Skolem number of a graph is smallest number n such that there exists a proper Skolem labelling only using the positive integers less than or equal to n. In this paper, we will begin by proving the Skolem number for another family of subgraphs of the hexagonal lattice and then prove the Skolem number for two families of subgraphs of the Kagome Lattice. © 2025 Georgia Southern University. All rights reserved.
Keywords: dept.mat

On Tight 6-Cycle Decompositions of Complete 3-Uniform Multi-Hypergraphs - Bandell, Jessica A.; Bunge, Ryan C.; Darrow, Brian D.; El-Zanati, Saad I.; Mountain, Claire E.; Neiburger, Levi (Springer Proceedings in Mathematics and Statistics, 2025)
The λ-fold complete 3-uniform hypergraph on v vertices has the edge multiset consisting of λ copies of each 3-element subset of its vertex set. A tight 6-cycle, denoted TC6, is a hypergraph with vertex set {a,b,c,d,e,f} and edge set {{a,b,c},{b,c,d},{c,d,e},{d,e,f},{e,f,a},{f,a,b}}. We give necessary and sufficient conditions on v for the existence of a TC6-decomposition of the λ-fold complete 3-uniform hypergraph on v vertices for any positive integer λ. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Journal Abbreviation: Springer Proc. Math. Stat.
Keywords: 3-uniform; Combinatorics; Computer science; Decomposition; Hypergraph; Mathematics; Multi-hypergraph; dept.mat

Identifying which clients will cancel their insurance policy machine learning methods - Narain, K.; Pang, Y. (Proceedings - 2024 IEEE 48th Annual Computers, Software, and Applications Conference, COMPSAC 2024, 2024)
Using the 2013 data set provided by Insurance Inc., logistic regression and linear discriminant analysis models were created along with data visualizations to find out which factors recorded in the data set and the state of those factors causes a client to cancel their policy. The factors that impact whether a client will cancel are those that directly pertain to the policy. For example, the coverage type and the premium the client is paying for the policy impacts the probability the client will cancel their policy. Factors that go into forming the policy and have a relationship between one another such as age and premium, also impact the probability that a client will cancel their policy. The credit status of a client, whether it is low, medium, or high, and the type of coverage they have, has the most impact on a client's inevitability to cancel. If a client's credit score is classified as low, then that client is has a high probability of cancelling their policy according to the LDA (Linear Discriminant Analysis) classifier and logistic regression model. Likewise, if a client has coverage type B, the probability that they will cancel their policy is higher. The sales channel used to sell a client a policy also impacts the probability they will cancel. According to the LDA classifier and the logistic regression model, if a client was sold a policy over the phone, they are more likely to cancel. © 2024 IEEE.
Keywords: Gaussian Distribution; Linear Discriminant Analysis (LDA) Classifier; Logistic Regression; Naive Bayes Classifier; dept.mat

Language Learning Outcomes in on Ground Vs. Online Settings: Comparison and Correlation - Tu, I Ju; Bartlett, Andrew (American Journal of Distance Education, 2024)
While the effectiveness of online instruction has been well established, there remains a limited understanding of the correlation between language skills and performance across various instructional sections. This study investigates the language proficiency outcomes of college students in online and on-ground language instruction, focusing on four essential language skills: Reading, Writing, Listening, and Speaking. Data were collected from students enrolled in third-semester language courses in French, German, Italian, and Spanish during the Spring semesters of 2019 and 2021 with on-ground and online instruction respectively in a public university in the United States. Descriptive statistics, the Kruskal-Wallis test, and pairwise correlation analysis were used to analyze the students’ performance in both modalities. The results indicate that students generally outperformed in the online modality, demonstrating a significantly higher positive correlation range compared to on-ground instruction. This finding suggests that multi-modality language instruction has the potential to foster more integrated and cohesive language proficiency development. The implications firstly show the positive correlation range in the online modality indicates that college instructors may be more capable of implementing effective online teaching methods due to various reasons. Secondly, college students’ potential for self-directed learning in the online setting may contribute to their enhanced outcomes. However, the study also reveals challenges for less taught languages, such as the need for additional support in terms of resource curation and networking opportunities for instructors.
_eprint: https://doi.org/10.1080/08923647.2024.2366594
Keywords: dept.mat; peer-reviewed

Reactive axillary lymph nodes after COVID-19 mRNA vaccination: Comparison of mRNA vs. attenuated whole-virus vaccines - Adin, M.E.; Isufi, E.; Wu, J.; Pang, Y.; Nguyen, D.; Simsek Has, D.; Caner, C.; Aboueldaha, N.; Mossa-Basha, M.; Pucar, D. (Nuclear Medicine Communications, 2024)
Objective To compare the incidence and natural course of reactive axillary lymph nodes (RAL) between mRNA and attenuated whole-virus vaccines using Deauville criteria. Methods In this multi-institutional PET-CT study comprising multiple vaccine types (Pfizer-BioNTech/Comirnaty, Moderna/Spikevax, Sinovac/CoronaVac and Janssen vaccines), we evaluated the incidence and natural course of RAL in a large cohort of oncological patients utilizing a standardized Deauville scaling system (n=522; 293 Female, Deauville 3-5 positive for RAL). Univariate and multivariate analyses were conducted to evaluate the predictive value of clinical parameters (absolute neutrophil count [ANC], platelets, age, sex, tumor type, and vaccine-to-PET interval) for PET positivity. Results Pfizer-BioNTech/Comirnaty and Moderna vaccines revealed similar RAL incidences for the first 20 days after the second dose of vaccine administration (44% for the first 10 days for both groups, 26% vs. 20% for 10-20 days, respectively for Moderna and Pfizer). However, Moderna recipients revealed significantly higher incidences of RAL after 20 days compared to Pfizer-BioNTech/Comirnaty, with nodal reactivity spanning up to the 9th week post-vaccination (15% vs. 4%, respectively P<0.001). No RAL was observed in patients who received either a single dose of J&J vaccine or two doses of CroronaVac. Younger patients showed increased likelihood of RAL, otherwise, clinical/demographic parameters were not predictive of RAL (P=0.014 for age, P>0.05 for additional clinical/demographic parameters). Conclusion RAL based on strict PET criteria was observed with mRNA but not with attenuated whole-virus vaccines, in line with higher immunogenicity and stronger protection offered by mRNA vaccines. © 2024 Wolters Kluwer Health. All rights reserved.
Keywords: COVID-19; CoronaVac; Janssen; axillary lymph node; dept.mat; mRNA vaccine; peer-reviewed

Identification of adipogenic and osteogenic differentiation using transfer learning of ResNet-18 - Mai, M.; Luo, S.; Wang, S.; Pang, Y. (Proceedings - 22nd IEEE International Conference on Machine Learning and Applications, ICMLA 2023, 2023)
Human mesenchymal stem cells (hMSCs) have great potential in cell-based therapies and regenerative medicine due to their self-renewal and multipotency. hMSCs can be differentiated into several cell types, including adipocytes and osteblast. Conventional approaches for determining adipocyte formation include staining of lipid droplets (i.e., oil-red-O) during adipogenesis, which is time-consuming and uneconomical. Thus, there is an emerging need for a more effective and accurate approach to the prediction of adipogenic differentiation. Here, by combining live-cell imaging with a deep learning method, we developed a convolutional neural network-based approach to precisely predict lipid droplet formation during adipogenic differentiation of hMSCs. © 2023 IEEE.
Keywords: Adipogenic differentiation; CNN; Deep learning; ResNet; Transfer learning; adipogenisis; computer vision; convolution; dept.mat; hMSCs; human mesenchymal stem cells; osteogenic differentiation

Embracing bilingualism: L1 retention amidst L2 acquisition - Sorokina, A.; Mugno, R. (Language Learning Journal, 2024)
In L1 attrition research, it's recognized that a previously acquired language can transform under the influence of a newly acquired one. However, the precise L1-L2 relationship is intricate and warrants further study. Some research suggest that L2 mastery might reduce L1 proficiency, while others show that both languages can be maintained. Age of onset and L1 use are the factors that have been discussed in the debate surrounding L1 attrition. The study aims to contribute to the ongoing discussion by examining L1 and L2 proficiency of Russian-English bilingual speakers (N = 35). The participants with comparable L2 proficiency but various degrees of L1 attrition who arrived at different ages and differed in their frequency of L1 use were recruited for the study. This diverse group provided an ideal quality sample for investigating the role of age of onset and L1 use, as well as the interplay between L1 and L2. By comparing L1 and L2 lexical diversity, syntactic complexity, and fluency, the study revealed that higher L2 proficiency was not associated with lower levels of L1 proficiency, suggesting that L1 retention is possible amidst L2 acquisition. L1 use played a more significant role in the L1 maintenance of these bilingual individuals. © 2024 Association for Language Learning.
Keywords: L1 attrition; L1 maintenance; L1 use; age of onset; bilingualism; dept.mat; dept.wll; peer-reviewed

Best Darn Statistics Workbook Ever - Hauselt, William J.; Mugno, Raymond (Kendall Hunt Publishing, 2021)
Keywords: dept.mat; dept.psy

Skolem Number of Subgraphs on the Triangular Lattice - Carrigan, Braxton; Green, Garrett (Communications on Number Theory and Combinatorial Theory, 2021)
Keywords: dept.mat; peer-reviewed

Morphology-based deep learning approach for predicting adipogenic and osteogenic differentiation of human mesenchymal stem cells (hMSCs) - Mai, Maxwell; Luo, Shuai; Fasciano, Samantha; Oluwole, Timilehin Esther; Ortiz, Justin; Pang, Yulei; Wang, Shue (Frontiers in Cell and Developmental Biology, 2023)
Human mesenchymal stem cells (hMSCs) are multipotent progenitor cells with the potential to differentiate into various cell types, including osteoblasts, chondrocytes, and adipocytes. These cells have been extensively employed in the field of cell-based therapies and regenerative medicine due to their inherent attributes of self-renewal and multipotency. Traditional approaches for assessing hMSCs differentiation capacity have relied heavily on labor-intensive techniques, such as RT-PCR, immunostaining, and Western blot, to identify specific biomarkers. However, these methods are not only time-consuming and economically demanding, but also require the fixation of cells, resulting in the loss of temporal data. Consequently, there is an emerging need for a more efficient and precise approach to predict hMSCs differentiation in live cells, particularly for osteogenic and adipogenic differentiation. In response to this need, we developed innovative approaches that combine live-cell imaging with cutting-edge deep learning techniques, specifically employing a convolutional neural network (CNN) to meticulously classify osteogenic and adipogenic differentiation. Specifically, four notable pre-trained CNN models, VGG 19, Inception V3, ResNet 18, and ResNet 50, were developed and tested for identifying adipogenic and osteogenic differentiated cells based on cell morphology changes. We rigorously evaluated the performance of these four models concerning binary and multi-class classification of differentiated cells at various time intervals, focusing on pivotal metrics such as accuracy, the area under the receiver operating characteristic curve (AUC), sensitivity, precision, and F1-score. Among these four different models, ResNet 50 has proven to be the most effective choice with the highest accuracy (0.9572 for binary, 0.9474 for multi-class) and AUC (0.9958 for binary, 0.9836 for multi-class) in both multi-class and binary classification tasks. Although VGG 19 matched the accuracy of ResNet 50 in both tasks, ResNet 50 consistently outperformed it in terms of AUC, underscoring its superior effectiveness in identifying differentiated cells. Overall, our study demonstrated the capability to use a CNN approach to predict stem cell fate based on morphology changes, which will potentially provide insights for the application of cell-based therapy and advance our understanding of regenerative medicine.
Keywords: dept.mat

Briefly Recalling Some Antecedents of Standards-Based Reform and Standardized Assessment in American Mathematics Education - Darrow, Brian (Journal of Mathematics Education at Teachers College, 2023)
Num Pages: 6
Keywords: dept.mat; peer-reviewed

A review of machine learning applications in life cycle assessment studies - Romeiko, Xiaobo Xue; Zhang, Xuesong; Pang, Yulei; Gao, Feng; Xu, Ming; Lin, Shao; Babbitt, Callie (Science of The Total Environment, 2023)
Life Cycle Assessment (LCA) is a foundational method for quantitative assessment of sustainability. Increasing data availability and rapid development of machine learning (ML) approaches offer new opportunities to advance LCA. Here, we review current progress and knowledge gaps in applying ML techniques to support LCA, and identify future research directions for LCAs to better harness the power of ML. This review analyzes forty studies reporting quantitative assessment with a combination of LCA and ML methods. We found that ML approaches have been used for generating life cycle inventories, computing characterization factors, estimating life cycle impacts, and supporting life cycle interpretation. Most of the reviewed studies employed a single ML method, with artificial neural networks (ANNs) as the most frequently applied approach. Both supervised and unsupervised ML techniques were used in LCA studies. For studies using supervised ML, training datasets were derived from diverse sources, such as literature, lab experiments, existing databases, and model simulations. Over 70 % of these reviewed studies trained ML models with less than 1500 sample datasets. Although these reviewed studies showed that ML approaches help improve prediction accuracy, pattern discovery and computational efficiency, multiple areas deserve further research. First, continuous data collection and compilation is needed to support more reliable ML and LCA modeling. Second, future studies should report sufficient details regarding the selection criteria for ML models and present model uncertainty analysis. Third, incorporating deep learning models into LCA holds promise to further improve life cycle inventory and impact assessment. Finally, the complexity of current environmental challenges calls for interdisciplinary collaborative research to achieve deep integration of ML into LCA to support sustainable development.
Keywords: Life cycle assessment; Machine learning; Model selection; Prediction; Sustainability; dept.mat; peer-reviewed

Inter-Pass Motion Correction for Whole-Body Dynamic PET and Parametric Imaging - Guo, Xueqi; Wu, Jing; Chen, Ming-Kai; Liu, Qiong; Onofrey, John A.; Pucar, Darko; Pang, Yulei; Pigg, David; Casey, Michael E.; Dvornek, Nicha C.; Liu, Chi (IEEE Transactions on Radiation and Plasma Medical Sciences, 2023)
Whole-body dynamic fluoro-D-glucose (FDG)-positron emission tomography (PET) imaging through continuous-bed-motion (CBM) mode multi-pass acquisition protocol is a promising metabolism measurement. However, inter-pass misalignment originating from body movement could degrade parametric quantification. We aim to apply a non-rigid registration method for inter-pass motion correction in whole-body dynamic PET. 27 subjects underwent a 90-min whole-body FDG CBM PET scan on a Biograph mCT (Siemens Healthineers), acquiring 9 over-the-heart single-bed passes and subsequently 19 CBM passes (frames). The inter-pass motion correction was executed using non-rigid image registration with multi-resolution, B-spline free-form deformations. The parametric images were then generated by Patlak analysis. The overlaid Patlak slope K_i and y-intercept V_b images were visualized to qualitatively evaluate motion impact and correction effect. The normalized weighted mean-squared Patlak fitting errors (NFEs) were compared in the whole body, head, and hypermetabolic regions of interest (ROIs). In K_i images, ROI statistics were collected and malignancy discrimination capacity was estimated by the area under the receiver operating characteristic curve (AUC). After the inter-pass motion correction was applied, the spatial misalignment appearance between K_i and V_b images was successfully reduced. Voxel-wise normalized fitting error maps showed global error reduction after motion correction. The NFE in the whole body ( p \,\,= 0.0013), head ( p \,\,= 0.0021), and ROIs ( p \,\,= 0.0377) significantly decreased. The visual performance of each hypermetabolic ROI in K_i images was enhanced, while 3.59% and 3.67% average absolute percentage changes were observed in mean and maximum K_i values, respectively, across all evaluated ROIs. The estimated mean K_i values had substantial changes with motion correction ( p \,\,= 0.0021). The AUC of both mean K_i and maximum K_i after motion correction increased, possibly suggesting the potential of enhancing oncological discrimination capacity through inter-pass motion correction.
Conference Name: IEEE Transactions on Radiation and Plasma Medical Sciences
Keywords: dept.mat; peer-reviewed

Autonomic modulation, spontaneous baroreflex sensitivity and fatigue in young men after COVID-19 - Latchman, Peter L; Yang, Qin; Morgenthaler, Diane; Kong, Lingsong; Sebagisha, J.; Melendez, Luke; Green, Cheryl A.; Bernard, Stanley; Mugno, Raymond; De Meersman, Ronald (Physiological research, 2023)
Impaired autonomic modulation and baroreflex sensitivity (BRS) have been reported during and after COVID-19. Both impairments are associated with negative cardiovascular outcomes. If these impairments were to exist undetected in young men after COVID-19, they could lead to negative cardiovascular outcomes. Fatigue is associated with autonomic dysfunction during and after COVID-19. It is unclear if fatigue can be used as an indicator of impaired autonomic modulation and BRS after COVID-19. This study aims to compare parasympathetic modulation, sympathetic modulation, and BRS between young men who had COVID-19 versus controls and to determine if fatigue is associated with impaired autonomic modulation and BRS. Parasympathetic modulation as the high-frequency power of R-R intervals (lnHFR-R), sympathetic modulation as the low-frequency power of systolic blood pressure variability (LFSBP), and BRS as the -index were measured by power spectral density analysis. These variables were compared between 20 young men who had COVID-19 and 24 controls. Independent t-tests and Mann-Whitney U tests indicated no significant difference between the COVID-19 and the control group in: lnHFR-R, P=0.20; LFSBP, P=0.11, and -index, P=0.20. Fatigue was not associated with impaired autonomic modulation or BRS. There is no difference in autonomic modulations or BRS between young men who had COVID-19 compared to controls. Fatigue did not seem to be associated with impaired autonomic modulation or impaired BRS in young men after COVID-19. Findings suggest that young men might not be at increased cardiovascular risk from COVID-19-related dysautonomia and impaired BRS.
1 citations (Crossref) [2023-10-31]
Keywords: Autonomic Nervous System; Baroreflex; Blood Pressure; COVID-19; Cardiovascular System; Heart Rate; Humans; Male; dept.hms; dept.mat; dept.nur; dept.pch; dept.ss; peer-reviewed

Residual intersections and core of modules - Costantini, Alessandra; Fouli, Louiza; Hong, Jooyoun (Journal of Algebra, 2023)
We introduce the notion of residual intersections of modules and prove their existence. We show that projective dimension one modules have Cohen-Macaulay residual intersections, namely they satisfy the relevant Artin-Nagata property. We then establish a formula for the core of orientable modules satisfying certain homological conditions, extending previous results of Corso, Polini, and Ulrich on the core of projective one modules. Finally, we provide examples of classes of modules that satisfy our assumptions.
0 citations (Crossref) [2023-10-31]
Keywords: Core; Reductions; Residual intersections; dept.mat; peer-reviewed

Application of Time Series Analysis Methods to Assess the impact of COVID-19 on Carbon Dioxide Emission Reduction in Connecticut - Kiernan, Katherine A.; Wu, Hao; Mugno, Ray; Pang, Yulei (2022 IEEE International Conference on Big Data (Big Data), 2022)
The primary goals of this study are to determine if the datasets of positive COVID-19 test cases and CO2 emissions from Connecticut over the span of March 24th, 2020-October 31, 2021 are in any ways correlated. With climate change a prominent issue facing the entire world today, it is important to explore methods of providing records of past patterns of greenhouse gas emissions in order to inform decision making that could reduce future ones. Autoregressive integrated moving average (ARIMA) modeling is also implemented in this paper to provide forecasting based on CO2 emissions in CT starting from 2019. The most significant results from this paper are as follows: the CO2 emission data of transportation sectors including ground transportation, domestics aviation, and international aviation and weekly COVID-19 positive test cases data has a strong relationship during the first 28 weeks of the pandemic with a correlation of -86.34%. The CO2 emissions experienced on average a -22.96% change of pre-pandemic vs during initial quarantine conditions and at most a - 44.48% change when comparing the pre-pandemic mean to the during initial quarantine minimum value. Lastly, the ARIMA model found to have the lowest Akaike information criterion (AIC) was ARIMA (4,0,4). In conclusion, in the event of a collective global pandemic and lockdown conditions, less traveling resulting in a correlated decrease of CO2 emissions. This means that perhaps concentrated efforts on reducing unnecessary travel could help mitigate the levels of carbon dioxide emissions as a more long-term solution to climate change opposed to the pandemic’s short-term example.
0 citations (Crossref) [2023-10-31]
Keywords: ARIMA; CO2 emission; COVID-19; Carbon dioxide; Change points detection; Climate change; Correlation coefficient; Decision making; Greenhouse effect; Pandemics; Time series analysis; dept.csc; dept.mat

A norm functor for quadratic algebras - Biesel, Owen (Beiträge zur Algebra und Geometrie / Contributions to Algebra and Geometry, 2022)
Given commutative, unital rings $$\mathcal {A}$$and $$\mathcal {B}$$with a ring homomorphism $$\mathcal {A}\rightarrow \mathcal {B}$$making $$\mathcal {B}$$free of finite rank as an $$\mathcal {A}$$-module, we can ask for a “trace” or “norm” homomorphism taking algebraic data over $$\mathcal {B}$$to algebraic data over $$\mathcal {A}$$. In this paper we we construct a norm functor for the data of a quadratic algebra: given a locally-free rank-2 $$\mathcal {B}$$-algebra $$\mathcal {D}$$, we produce a locally-free rank-2 $$\mathcal {A}$$-algebra $$\textrm{Nm}_{\mathcal {B}/\mathcal {A}}(\mathcal {D})$$in a way that is compatible with other norm functors and which extends a known construction for étale quadratic algebras. We also conjecture a relationship between discriminant algebras and this new norm functor.
0 citations (Crossref) [2023-10-31]
Keywords: 11R11; 13B02; 13B40; 13C10; 14B25; Algebra of finite rank; Norm functor; Quadratic algebra; Ring extension; dept.mat; Étale algebra

Generalization of bi-canonical degrees - Brennan, J.; Ghezzi, L.; Hong, J.; Vasconcelos, W. V. (São Paulo Journal of Mathematical Sciences, 2023)
We discuss invariants of Cohen-Macaulay local rings that admit a canonical module $$\omega$$. Attached to each such ring R, when $$\omega$$is an ideal, there are integers–the type of R, the reduction number of $$\omega$$–that provide valuable metrics to express the deviation of R from being a Gorenstein ring. In (Ghezzi et al. in JMS 589:506–528, 2017) and (Ghezzi et al. in JMS 571:55–74, 2021) we enlarged this list with the canonical degree and the bi-canonical degree. In this work we extend the bi-canonical degree to rings where $$\omega$$is not necessarily an ideal. We also discuss generalizations to rings without canonical modules but admitting modules sharing some of their properties.
Keywords: 13A99; Bi-canonical degree; Canonical module; Primary 13H15; Secondary 13H10; dept.mat; peer-reviewed

Deformations of reducible SL(n, C) representations of fibered 3-manifold groups - Kozai, K. (Osaka Journal of Mathematics, 2022)
Let Mφ be a surface bundle over a circle with monodromy φ: S → S. We study deformations of certain reducible representations of π1(Mφ)intoSL(n, C), obtained by composing a reducible representation into SL(2, C) with the irreducible representation SL(2, C) → SL(n, C). In particular, we show that under certain conditions on the eigenvalues of φ∗, the reducible representation is contained in a (n + 1 + k)(n − 1) dimensional component of the representation variety, where k is the number of components of ∂Mφ . This result applies to mapping tori of pseudo-Anosov maps with orientable invariant foliations whenever 1 is not an eigenvalue of the induced map on homology, where the reducible representation is also a limit of irreducible representations. © 2022, Osaka University. All rights reserved.
Keywords: dept.mat; ⛔ No DOI found

Comparative assessment of shell properties in eight species of cohabiting unionid bivalves - Prezant, Robert S.; Dickinson, Gary H.; Chapman, Eric J.; Mugno, Raymond; Rosen, Miranda N.; Cadmus, Maxx B. (Freshwater Mollusk Biology and Conservation, 2022)
Freshwater unionid mussels produce a bilayered shell with the mineral proportion comprising an outer prismatic and an inner nacreous layer. The shell is the animals’ primary structural means of protection from predators and environmental challenges; therefore, variations in shell strength and properties may lead to differences in survival. Few studies have systematically assessed shell properties in unionids. A major challenge in such work is separating effects of environment from those of evolutionary history, because ultimately, both can affect shell properties. We collected eight species of unionids within a small area of the Allegheny River, Pennsylvania, that was relatively homogeneous in substratum type and other environmental characteristics. For each species, we quantified shell thickness, including thickness of the prismatic and nacreous layers, and shell micromechanical properties (microhardness and crack propagation, a measure of fracture resistance) in three regions of the shell. Shell thickness varied dramatically among species and was about five times greater in the thickest-shelled species, Pleurobema sintoxia, than in the thinnest-shelled species, Villosa iris. Because all species experienced similar environmental conditions, variation in shell thickness can be attributed largely to evolutionary history. In contrast, microhardness and crack propagation showed little variation among species. Given that micromechanical properties are similar among species, shell strength may be largely a function of thickness. These results have conservation implications, as differences in shell thickness could reflect relative vulnerability to predators and physical conditions
0 citations (Crossref) [2023-10-31]
Keywords: dept.aa; dept.mat; peer-reviewed

Secondary Teacher Candidates’ Mathematical Modeling Task Design and Revision - Kim, Dong-Joong; Choi, Sang-Ho; Lee, Younhee; Lim, Woong (Mathematics, 2021)
The purpose of this study is to investigate secondary teacher candidates’ experience of mathematical modeling task design. In the study, 54 teacher candidates in a university-based teacher education program created modeling tasks and scoring rubrics. Next, the participants pilot-tested the tasks with students and had the opportunity to revise the original tasks and rubrics based on student responses. The data included participants’ statements, in which they described and reflected on the design and revision process of modeling tasks. The study describes six didactic revision strategies in revising modeling tasks and identifies five emerging pedagogical ideas from revising tasks and rubrics. The study also discusses the way modeling task design activities have the potential to support teacher candidates’ learning through a bottom-up modeling curriculum in teacher education.
1 citations (Crossref) [2023-10-31] Number: 22
Keywords: dept.mat; didactic revision strategy; mathematical modeling task design; peer-reviewed; secondary teacher candidates

A Comprehensive Astrometric Calibration of HST's WFPC2. I. Distortion Mapping - Casetti-Dinescu, Dana I.; Girard, Terrence M.; Kozhurina-Platais, Vera; Platais, Imants; Anderson, Jay; Horch, Elliott P. (Publications of the Astronomical Society of the Pacific, 2021)
Wide field planetary camera 2 (WFPC2) exposures are already some 20 years older than Gaia epoch observations, or future James Webb Space Telescope observations. As such, they offer an unprecedented time baseline for high-precision proper-motion studies, provided the full astrometric potential of these exposures is reached. We have started such a project with the work presented here being its first step. We explore geometric distortions beyond the well-known ones published in the early 2000 s. This task is accomplished by using the entire database of WFPC2 exposures in filters F555W, F606W and F814W and three standard astrometric catalogs: Gaia EDR3, 47 Tuc and ωCen. The latter two were constructed using Hubble Space Telescope observations made with cameras other than WFPC2. We explore a suite of centering algorithms, and various distortion maps in order to understand and quantify their performance. We find no high-frequency systematics beyond the 34th-row correction, down to a resolution of 10 pixels. Low-frequency systematics starting at a resolution of 50 pixels are present at a level of 30–50 millipix (1.4–2.3 mas) for the PC and 20–30 millipix (2–3 mas) for the WF chips. We characterize these low-frequency systematics by providing correction maps and updated cubic-distortion coefficients for each filter.
3 citations (Crossref) [2023-10-31]
Keywords: dept.mat; dept.phy; peer-reviewed

Constructing (3, B)-sudoku pair latin squares - Carrigan, Braxton; Diaz, David; Hammer, James; Lorch, John (Australasian Journal of Combinatorics, 2022)
An (a, b)-Sudoku pair Latin square is a Latin square that is simult-aneously an (a, b)-Sudoku Latin square and a (b, a)-Sudoku Latin square. While (a, b)-Sudoku Latin squares are known to exist for any positive integers a and b, the pairs a, b for which an (a, b)-Sudoku pair Latin square exists are largely unknown. In this article we establish the existence of (a, b)-Sudoku pair Latin squares for an infinite collection of pairs (a, b). Our results show that a (3, b)-Sudoku pair Latin square can be constructed for any positive integer b. ©The author(s).
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85121634938
Keywords: dept.mat; peer-reviewed; ⛔ No DOI found

Portraying mathematics pre-service teachers’ experience of creating video lessons with portable interactive whiteboards through the TPACK - Bonafini, Fernanda Cesar; Lee, Younhee (The New Educator, 2021)
This study investigates how pre-service teachers use their knowledge of technology, mathematics, and pedagogy to create video lessons using portable interactive whiteboards. The TPACK framework was used to identify the different types of knowledge pre-service teachers rely on as they create their videos. Results indicate pre-service teachers’ effective use of conveyance technology, pedagogical techniques, and mathematical representations using technology. Their videos portray their process of coordinating their TPACK. Recommendations are made for teacher educators to integrate technology in activities that aim to develop pre-service teachers’ comfort and confidence with technological tools for teaching and learning. © 2021 ATE and CCNY.
0 citations (Crossref) [2023-10-31]
Keywords: dept.mat; peer-reviewed

CT-free attenuation correction for dedicated cardiac SPECT using a 3D dual squeeze-and-excitation residual dense network. - Chen, Xiongchao; Zhou, Bo; Shi, Luyao; Liu, Hui; Pang, Yulei; Wang, Rui; Miller, Edward J.; Sinusas, Albert J.; Liu, Chi (Journal of nuclear cardiology : official publication of the American Society of Nuclear Cardiology, 2021)
Background: Attenuation correction (AC) using CT transmission scanning enables the accurate quantitative analysis of dedicated cardiac SPECT. However, AC is challenging for SPECT-only scanners. We developed a deep learning-based approach to generate synthetic AC images from SPECT images without AC. Methods: CT-free AC was implemented using our customized Dual Squeeze-and-Excitation Residual Dense Network (DuRDN). 172 anonymized clinical hybrid SPECT/CT stress/rest myocardial perfusion studies were used in training, validation, and testing. Additional body mass index (BMI), gender, and scatter-window information were encoded as channel-wise input to further improve the network performance. Results: Quantitative and qualitative analysis based on image voxels and 17-segment polar map showed the potential of our approach to generate consistent SPECT AC images. Our customized DuRDN showed superior performance to conventional network design such as U-Net. The averaged voxel-wise normalized mean square error (NMSE) between the predicted AC images by DuRDN and the ground-truth AC images was 2.01 ± 1.01%, as compared to 2.23 ± 1.20% by U-Net. Conclusions: Our customized DuRDN facilitates dedicated cardiac SPECT AC without CT scanning. DuRDN can efficiently incorporate additional patient information and may achieve better performance compared to conventional U-Net. © 2021, American Society of Nuclear Cardiology.
23 citations (Crossref) [2023-10-31] http://www.ncbi.nlm.nih.gov/pubmed/34085168 ; https://www.ncbi.nlm.nih.gov/pubmed/34085168 ; https://pubmed.ncbi.nlm.nih.gov/34085168/ ; https://europepmc.org/article/MED/34085168
Keywords: adult; article; body mass; controlled study; deep learning; dept.mat; excitation; female; gender; human; male; myocardial perfusion imaging; patient information; peer-reviewed; physiological stress; qualitative analysis; quantitative analysis; single photon emission computed tomography; x-ray computed tomography

Inter-pass motion correction for whole-body dynamic parametric PET imaging - Guo, Xueqi; Wu, Jing; Chen, Ming-Kai; Onofrey, John A.; Pang, Yulei; Pigg, David; Casey, Michael E.; Dvornek, Nicha C.; Liu, Chi (The Journal of Nuclear Medicine, 2021)
Keywords: dept.mat; peer-reviewed; ⛔ No DOI found

Skolem number of cycles and grid graphs - Carrigan, Braxton; Asplund, John (Theory and Applications of Graphs, 2021)
A Skolem sequence can be thought of as a labelled path where two vertices with the samelabelarethatdistanceapart.Thisconcepthasnaturallybeengeneralizedto labellingsofothergraphs,butalwaysusingatmosttwoofanyintegerlabel.Giventhat more than two vertices can be mutually distance d apart, wedefine a new generalization of aSkolemsequenceongraphsthatwecallaproperSkolemlabelling.Thisbrings rise tothequestion;use to proper Skolemlabel a graph?"This will be known as the Skolem number of the graph. In this paper we give the Skolem number for cycles and grid graphs,while also providing other related results along the way. Published by Digital Commons@Georgia Southern, 2021. © 2021 Georgia Southern University. All rights reserved.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85115356208
Keywords: dept.mat; peer-reviewed

List colorings count rokudoku-pair squares - Carrigan, Braxton; Hammer, James; Lorch, John; Lorch, Robert; Owens, Caitlin (Bulletin of the Institute of Combinatorics and its Applications, 2021)
A rokudoku-pair square is an order-6 sudoku Latin square for both 2 x 3 and 3 x 2 tiling regions simultaneously. We count the distinct rokudoku-pair squares as well as orbits under the action of a suitable group. Our arguments employ group actions and list colorings of graphs. As an application we determine which rokudoku-pair squares are based on groups. © 2021. All Rights Reserved.
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85109428650
Keywords: dept.mat; peer-reviewed; ⛔ No DOI found

Comparing the performance on the MI and SAT/PSAT for the purpose of monitoring student achievement - McDonald, Michael; Pang, Yulei (International Journal of Information and Education Technology, 2021)
This paper will discuss the correlation between the SAT and the Math Inventory Test. Many school districts adopted the Math Inventory as a tool to measure student growth from grades kindergarten through high school. The Math Inventory is a computer-administered test that gives students math problems spanning from counting to high school level math. When completed, the students are given a quantile measure, much like a Lexile score for reading skill. The purpose of this study is to figure out if success on the Math Inventory is a good indicator for performing well on the SAT. For most high schools around the United States, objectives and lessons are aligned with those of the SAT. The goal of high school teachers is for students to excel on the SAT so that they can go to college, which means the tests used in middle school should be aligned with that goal. If the Math Inventory is not, then it might not be a very good use of school time and resources. Data was analyzed from the 2017-2018 school year from ten different high schools in an urban school district to determine the correlation between Math Inventory score, and the math score/sub scores of SAT/PSAT. The value of the Pearson’s correlation coefficient is used to suggest a fairly moderate positive relationship between these two variables. © 2021, International Journal of Information and Education Technology. All rights reserved.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85121039102
Keywords: dept.mat; peer-reviewed

Investigating prospective teachers’ TPACK and their use of mathematical action technologies as they create screencast video lessons on iPads - Bonafini, Fernanda Cesar; Lee, Younhee (TechTrends : for leaders in education & training, 2021)
The increasing number of technological devices available in schools, aligned with curriculum guidance, set an expectation for mathematics teachers to incorporate these devices into their teaching. This qualitative study investigated prospective teachers’ use of TPACK and mathematical action technologies as they created screencast video lessons using iPads. Results showed prospective teachers’ effective use of pedagogical techniques and the screencast app as an amplifier tool, according to the amplifier-reorganizer metaphor. Half of the participants used mathematics technology to confirm and expand the results they had found without technology. The other half had mathematics technology integrated into their solution exercising the balance among TPACK components. For some, their use of the mathematical tool had the potential of expanding the mathematical repertoire of virtual students. We conclude by making recommendations for teacher educators to implement cycles of learning for pre-service teachers to design, enact, and reflect upon the creation of screencast video lessons. © 2021, Association for Educational Communications & Technology.
8 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85100189375
Keywords: dept.mat; peer-reviewed

Comparing Machine Learning Approaches for Predicting Spatially Explicit Life Cycle Global Warming and Eutrophication Impacts from Corn Production - Romeiko, Xiaobo Xue; Guo, Zhijian; Pang, Yulei; Lee, Eun Kyung; Zhang, Xuesong (Sustainability, 2020)
Agriculture ranks as one of the top contributors to global warming and nutrient pollution. Quantifying life cycle environmental impacts from agricultural production serves as a scientific foundation for forming effective remediation strategies. However, methods capable of accurately and efficiently calculating spatially explicit life cycle global warming (GW) and eutrophication (EU) impacts at the county scale over a geographic region are lacking. The objective of this study was to determine the most efficient and accurate model for estimating spatially explicit life cycle GW and EU impacts at the county scale, with corn production in the U.S.’s Midwest region as a case study. This study compared the predictive accuracies and efficiencies of five distinct supervised machine learning (ML) algorithms, testing various sample sizes and feature selections. The results indicated that the gradient boosting regression tree model built with approximately 4000 records of monthly weather features yielded the highest predictive accuracy with cross-validation (CV) values of 0.8 for the life cycle GW impacts. The gradient boosting regression tree model built with nearly 6000 records of monthly weather features showed the highest predictive accuracy with CV values of 0.87 for the life cycle EU impacts based on all modeling scenarios. Moreover, predictive accuracy was improved at the cost of simulation time. The gradient boosting regression tree model required the longest training time. ML algorithms demonstrated to be one million times faster than the traditional process-based model with high predictive accuracy. This indicates that ML can serve as an alternative surrogate of process-based models to estimate life-cycle environmental impacts, capturing large geographic areas and timeframes.
15 citations (Crossref) [2023-10-31] Number: 4
Keywords: Agriculture; Eutrophication; Global warming; Life cycle assessment; Machine learning; Midwest; Spatial assessment; United States; Zea mays; agricultural production; agriculture; crop production; dept.mat; eutrophication; global warming; life cycle analysis; life cycle assessment; machine learning; peer-reviewed; prediction; spatial analysis; spatial assessment

Learning from others: A low‐cost–high‐impact risk/opportunity identification technique - Williams, Brendan E.; Williams, Anne S.; Williams, Katherine M. (Journal of Healthcare Risk Management, 2020)
2 citations (Crossref) [2023-10-31]
Keywords: dept.mat; peer-reviewed

‘Is it wise to open up America again now?’ Learning from government responses to COVID-19 and economy reopen points in three Asia-Pacific countries - Yu, Jia; Pang, Yulei (British Journal of Healthcare Management, 2020)
With the continuously increasing number of new confirmed COVID-19 cases, many health experts worried about the possibility of a ‘second wave’ outbreak, which might cause more deaths and hit economies even worse. This article looks at the experiences of fighting COVID-19 from three Asia-Pacific countries and discusses whether it is a wise decision to open up America again at this time.
2 citations (Crossref) [2023-10-31] tex.ids: yuItWiseOpen2020a
Keywords: dept.eco; dept.mat; peer-reviewed

A regional Kronecker product and multiple-pair latin squares - Carrigan, Braxton; Hammer, James; Lorch, John (Discrete Mathematics, 2020)
We introduce a variant of the Kronecker product, called the regional Kronecker product, that can be used to build new, larger multiple-pair latin squares from existing multiple-pair latin squares. We present applications to the existence and orthogonality of multiple-pair latin squares. © 2019 Elsevier B.V.
2 citations (Crossref) [2023-10-31] tex.ids: carriganRegionalKroneckerProduct2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85076148310 type: Article
Keywords: Factor pair latin squares; Multiple pair latin squares; Sudoku pair latin squares; dept.mat; peer-reviewed

The bi-canonical degree of a Cohen–Macaulay ring - Ghezzi, Laura; Goto, Shiro; Hong, Jooyoun; Hutson, H. L.; Vasconcelos, Wolmer V. (Journal of Algebra, 2021)
This paper is a sequel to [8] where we introduced an invariant, called canonical degree, of Cohen–Macaulay local rings that admit a canonical ideal. Here to each such ring R with a canonical ideal, we attach a different invariant, called bi-canonical degree, which in dimension 1 appears also in [12] as the residue of R. The minimal values of these functions characterize specific classes of Cohen–Macaulay rings. We give a uniform presentation of such degrees and discuss some computational opportunities offered by the bi-canonical degree. © 2019 Elsevier Inc.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85059675393
Keywords: dept.mat; peer-reviewed